-دور التعليم العالي في تحقيق التنمية المستدامة دراسة حالة -جامعة الأغواط - بن مبارك حياة; كوريمي كنزة; قرادي عبد القادر (جامعة عمار ثليجي الاغواط, 2022)
This study aims to know the role of higher education in achieving sustainable development by referring to showing some of the developments that the university has witnessed, in addition to presenting, analyzing and commenting on the results. The university evaluates the effectiveness and efficiency of change in its faculties and institutes, and from here we realize that there is a close relationship between higher education and sustainable development, and development cannot achieve any step unless qualified human resources are available, and therefore the education process is the basis of the sustainable development process.